1992
DOI: 10.1159/000116835
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Low-Molecular Weight Antioxidants, Uric Acid, Tyrosine and Tryptophan in Plaques and White Matter from Patients with Multiple Sclerosis

Abstract: The levels of the antioxidants ascorbic acid, cysteine, reduced glutathione and a-tocopherol, of the free-radical marker uric acid and of the amino acids tyrosine and tryptophan were measured by means of high-pressure liquid chromatography in plaques, adjacent white matter and distant white matter from patients with multiple sclerosis, and in central nervous system tissue from patients without neurological diseases. Cholesterol and DNA were also determined, to check demyelination and cellularity. Uric acid was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 14 publications
1
44
1
2
Order By: Relevance
“…Some studies have suggested that serum or CSF UA levels decrease in MS (Dujmovic et al., 2009; Peng et al., 2008; Sotgiu et al., 2002), while others show increased UA and purine compounds in biological fluids of MS patients (Amorini et al., 2009; Langemann, Kabiersch, & Newcombe, 1992; Lazzarino et al., 2010). Min et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that serum or CSF UA levels decrease in MS (Dujmovic et al., 2009; Peng et al., 2008; Sotgiu et al., 2002), while others show increased UA and purine compounds in biological fluids of MS patients (Amorini et al., 2009; Langemann, Kabiersch, & Newcombe, 1992; Lazzarino et al., 2010). Min et al.…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect a compensatory mechanism to defend cells against oxidative stress. In another study, decreased levels of GSH were measured in plaques from MS patients (Langemann et al, 1992). Moreover, decrease of reduced GSH and increase oxidised GSH and S-nitrosothiols were found in CSF samples of MS patients (Calabrese et al, 2002).…”
Section: Thiol-based Antioxidantsmentioning
confidence: 90%
“…CSF vitamin E levels were not significantly different between MS patients during exacerbations as compared to controls, while serum levels of vitamin E indeed were lower in MS patients (Jimenez-Jimenez et al, 1998). In MS plaques, levels of glutathione (GSH) and vitamin E were significantly decreased as compared to adjacent and distant white matter (Langemann et al, 1992). From these studies, it can be concluded that systemic, CSF and brain tissue levels of several antioxidants indeed are altered in MS.…”
Section: Antioxidant Deficiencies In Msmentioning
confidence: 90%
“…There are indications that posttranslational oxidative modification of the enzyme may contribute to decreased CK-BB activity in the cerebral cortex in a number of neurodegenerative disorders, including Alzheimer's disease (Aksenov et al, 2000;Aksenov et al, 1999). In MS, there is increased production of reactive oxygen species, not only in focal inflammatory white-matter lesions (Langemann et al, 1992), Figure 1 (A) Schematic representation of the astrocyte phosphocreatine (PCr)-creatine (Cr) cycle. Mitochondrial creatine kinase (CK) ensures that adenosine triphosphate (ATP), produced by oxidative phosphorylation, is converted into PCr.…”
Section: Phosphocreatine Metabolismmentioning
confidence: 99%